Correlation between Passive Cigarette Smoke Exposure on Low Birth Weight: Meta-Analysis - Handriani, Winei; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Low birth weight (LBW) is defined as a newborn baby weighing less than 2500 grams. Low birth weight is a serious condition in developing countries. The impact of cigarette smoke on pregnant women who are exposed to cigarette smoke is at a higher risk of complications, such as miscarriage, premature birth, or babies born with low weight. This study aims to analyze the relationship between exposure to secondhand smoke and low birth weight. Subjects and Method: This research is a systematic review and meta-analysis by systematically reviewing primary articles from Pubmed, Google Scholar, Scient Direct and Springerlink by selecting articles published in 2012-2022. The articles searched using PICO were P: Pregnant women, I: exposed to cigarette smoke, C: not exposed to cigarette smoke, O: low birth weight. Keywords